Responsiveness of superficial hand veins to phenylephrine in essential hypertension. Alpha adrenergic blockade during prazosin therapy. - Eichler, H G (1989)
Patients with essential hypertension show an increase in vascular resistance. It is unclear whether this is caused by structural changes in the arterial wall or by hyperresponsiveness of vascular smooth muscle to endogenous alpha adrenergic agonists. Using the dorsal hand vein compliance technique we compared the changes in diameter of superficial veins in response to phenylephrine, an alpha 1 adrenergic receptor agonist, and to nitroglycerin, a venorelaxant, in patients with essential hypertension and in normotensive subjects. The dose of phenylephrine that produced 50% of maximal venoconstriction (ED50) in the hypertensive subjects was 257 ng/min (geometric mean; log mean +/- SD was 2.41 +/- 0.54). In the control subjects the ED50 was 269 ng/min (geometric mean; log mean was 2.43 +/- 0.43). Maximal response (Emax) for phenylephrine was 84 +/- 13% in the hypertensive subjects and 90 +/- 6% in the control subjects. Differences in the group means of the ED50 (P = 0.92) or the Emax (P = 0.27) were not significant. There were no significant differences in the ED50 (P = 0.54) or the Emax (P = 0.08) for nitroglycerin between the two groups. These results show no evidence for a generalized change in alpha adrenergic responsiveness in hypertension and support the concept that increased blood pressure responses to alpha adrenergic stimulation in hypertensives are due to structural and geometric changes in the arterial wall rather than to an increased responsiveness of postsynaptic alpha adrenergic receptors. The phenylephrine studies were repeated in seven hypertensive patients during treatment with prazosin, an alpha 1 adrenergic antagonist. The mean dose ratio of the shift in phenylephrine ED50 (ED50 during prazosin therapy/ED50 before prazosin therapy) was 6.1. This indicates that small doses of prazosin (1-2 mg) cause significant in vivo shifts in the dose-response relationship of alpha adrenergic agonists. The dorsal hand vein compliance technique is useful in detecting systemic effects of alpha adrenergic antagonists.